Nodulation and Morphological Response of Pueraria Javanica Bent. to Sunlight Intensity - Dina Puspita Sari; Amar Ma'ruf (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Pueraria javanica Bent. is a tropical leguminous ground cover crop commonly planted in oil palm plantations to reduce soil erosion, fix nitrogen, and suppress weed growth. This plant is known to be resistant to fluctuations in low and high light intensity. Pueraria javanica has the ability to induce nodule formation by growing root hairs on the main branched root through a symbiosis with the bacterium Bradyrhizobium japonicum, stimulating the root surface to encourage nodule entry. In addition, legumes have the ability to bind with soil rhizobial bacteria, which fix atmospheric N2. This is a form of N that is not available to plants, but can fix N2 from the soil. The aim of this study was to analyze the effect of variations in sunlight intensity on nodule formation in Pueraria javanica and to determine the effect of sunlight intensity on vegetative growth and morphological development of Pueraria javanica. This research was conducted at the Experimental Garden of Asahan University campus, Asahan Regency, North Sumatra Province, with an altitude of ± 25 meters above sea level from January to March 2025. The research was conducted using a randomized block design method consisting of paranet and IAA auxin treatments. The use of paranet was divided into four levels, namely control without paranet, paranet with transparency of 50%, 75%, and 95%. Meanwhile, the application of IAA auxin consisted of three concentration levels, namely 100 ppm, 200 ppm, and 300 ppm. The observed variables were: plant height, number of leaves, number of leaflets, leaf area, fresh weight of plants, root length, number of root nodules, fresh weight of roots, dry weight of roots. The analysis of significant differences was made using the Tukey's HSD method. All data analysis used the SPSS application version 16.0 (SPSS, Chicago, United States). The results of the study showed that the treatment of various percentages of paranet on Pueraria javanica showed a significant effect on all observation parameters with the best growth in the control treatment. The application of auxin on Pueraria javanica showed a significant difference in the number of leaves, number of leaflets, leaf area, fresh weight of plants, root length, number of root nodules, fresh weight of roots, dry weight of roots. With the best growth in the control treatment. The two treatments above between the treatment of paranet percentage and the administration of auxin showed an interaction that had a significant effect on several parameters observed, including the number of root nodules, fresh weight of roots and dry weight of roots